2020
DOI: 10.1111/dme.14401
|View full text |Cite
|
Sign up to set email alerts
|

Association between glycaemic outcome and BMI in Danish children with type 1 diabetes in 2000–2018: a nationwide population‐based study

Abstract: Aim To describe the development of HbA1c and BMI over time in Danish children with type 1 diabetes; and to investigate the association between HbA1c and BMI including influence of age, gender, diabetes duration, severe hypoglycaemia and treatment method. Methods We used the nationwide Danish Registry of Childhood and Adolescent Diabetes, DanDiabKids, including annual registrations of all children with diabetes treated at Danish hospitals. With linear mixed‐effects models and splines we analyzed the HbA1c and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Finally, the findings in this study also reported an association between increased BMI and total cholesterol level with higher HbA1c values. Although controversial results have been published, past work on children and adults with T1D have already reported a relationship between higher BMI and increased HbA1c levels [35][36][37]. Similarly, our results confirmed previous studies reporting high lipid levels in children and adult individuals with poorly controlled type 1 diabetes [38][39][40].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the findings in this study also reported an association between increased BMI and total cholesterol level with higher HbA1c values. Although controversial results have been published, past work on children and adults with T1D have already reported a relationship between higher BMI and increased HbA1c levels [35][36][37]. Similarly, our results confirmed previous studies reporting high lipid levels in children and adult individuals with poorly controlled type 1 diabetes [38][39][40].…”
Section: Discussionsupporting
confidence: 92%
“…A second result was the higher BMI‐SDS in teenage girls using the CSII regimen. This is consistent with the findings of Ibfelt et al 33 and Birkebaek et al 34 One explanation could be that girls with a high BMI‐SDS might have an insulin resistance, which can lead to a higher HbA1c prompting healthcare practitioners to provide them with CSII treatment in an attempt to improve their metabolic control. If this is the case, those involved in health care delivery to children with Type 1 diabetes should explore ways to prevent avoidable increases in BMI through support to patients and families, for example healthy food recommendations and encouragement to do physical activity.…”
Section: Discussionsupporting
confidence: 91%
“…Further, high BMI z ‐score 12,13 and overweight 14 was reported to be associated with poorer HbA 1c trajectories. We previously found a non‐linear relationship between HbA 1c and BMI z ‐score in Danish children with type 1 diabetes 24 . Furthermore, a review that included Schwandt et al 2017 21 and 10 smaller studies of children with type 1 diabetes ( n = 72–1449) also applying group‐based statistical methods reported that most studies found poor HbA 1c trajectories associated with fewer BGM, whereas age at diagnosis, sex and use of insulin pen versus pump was found to be a predictor in some but not other studies.…”
Section: Discussionmentioning
confidence: 97%
“…We previously found a non-linear relationship between HbA 1c and BMI z-score in Danish children with type 1 diabetes. 24 Furthermore, a review that included Schwandt et al trajectories. 25 In summary, our and other's findings suggest that sociodemographic, psychological and diabetes management factors are important in predicting HbA 1c patterns, whereas injection method had an effect in only some studies and was not found to be important in our longitudinal study in a Danish setting with free health care provided access to pump technology.…”
Section: Discussionmentioning
confidence: 99%